(untitled) (Tempo e Argumento, 2013)
This article presents an overview of the Coleção Documentos Brasileiros’ golden age (from the 1930s to the 1950s, contemporaneously to other similar projects) and intends to show how it housed authors and books committed to the production of a new knowledge about Brazil, particularly as regards to the History. Thus this editorial enterprise has set up also a privileged vehicle to the diffusion of new ways to approach the Brazilian past, playing an important role in the transforming scenario whereby the Brazilian historiography then was passing.